Relationship between toll-like receptor 8 gene polymorphisms and pediatric pulmonary tuberculosis - (:unkn) unknown (Hindawi Limited, 2011)
Objectives: Genetic variants in Toll-like receptors (TLRs) are considered a potential indicator for host susceptibility to and outcome of several infectious diseases including tuberculosis. The aim of this study was to determine whether -129 C/G and Met1Val polymorphisms of TLR8 were associated with pediatric pulmonary tuberculosis in Turkish population. Methods: The -129 C/G and Met1Val polymorphisms were studied in 124 children with pulmonary tuberculosis compared to 150 age-matched healthy control subjects. Results: We did not identify any statistically significant differences between the patients with TB and control groups with regard to the frequency of genotypes GG or G/(-), CG, and CC or C/(-); and alleles G and C at rs3764879 (p> 0.05). We found a strong association with genotype A/(-) at rs3764880 with susceptibility to pulmonary TB in males (OR 2.87, 95%CI 1.38-5.98, p=0.007). Conclusions: Our results provide evidence, for the first time, of a role for the TLR8 gene in susceptibility to pulmonary TB in male children. Additional research to verify our results are necessary. Tuberculosis in children presents particularly difficult challenges, but research priorities and advances in pediatric tuberculosis could provide wider insights and opportunities for tuberculosis control. © 2011 - IOS Press and the authors. All rights reserved.
Keywords: Children; pulmonary tuberculosis; single nucleotide polymorphism; Toll-like receptor 8